Islamic sustainable finance: the role of regulators - Hassan, Rusni; Ilias, Ibtisam @ Ilyana (Routledge, 2024)
The significance of sustainability in Islamic finance is proven when sustainability indicator has been chosen as one of the key indicators in the Islamic Financial Development Indicator 2021 (IFDI) which measures the Islamic finance industry's development status. The Sustainability Indicator is a weighted index of Corporate Social Responsibility (CSR) activities and environmental, social, and governance (ESG) practices for all Islamic finance sectors and asset classes. Malaysia ranked first in its Sustainability Indicator. This achievement is reinforced by the country’s drive for green and sustainable and responsible investment (SRI) sukuk along with. ESG-aligned Islamic funds such as for waqf (charitable endowment). Saudi Arabia is also among the active markets developing CSR and ESG-aligned Islamic finance sectors, especially in charity and zakat disbursement. Distinguished top countries are Singapore and South Africa which achieved high CSR and ESG scores led by some institutions such as Sabana Industrial Real Estate and Al-Baraka Bank South Africa. Jordan, on the other hand, is the second biggest disburser of CSR funds, especially Qard al-Hassan (benevolent loan). Figure 8.1 depicts that IFIs from various jurisdictions have intensified their endeavours to materialize ESG-oriented principles. It is submitted that the successful execution of ESG-related agenda does not merely rely on the individual financial institutions (FIs) but requires strong will and commitment of financial regulators. The financial regulators including central banks play overriding roles to support sustainable finance and address climate / change within the financial industry (Batten et al., 2016; Dikau & Volz, 2021).